[Mossy Sea Cliff Side in Heimaey] - Streng, Evelyn Fiedler (1975)
Photograph of a mossy sea cliff side along Heimaey. The brown, layered rocks sit along the grey cliff, green moss and grass covering the structures. A white wave moves away from the black water at the bottom of the photograph, crashing against a curved, moss covered rock at the center of the photograph.